Abd al-Fattāḥ al-Qāḍī's Critique of Ignác Goldziher's Thought on Qirā'āt: Its Implications for Qirā'āt Learning in Islamic Education Institutions - Ilmi, Moh. Hudal Hafid; Yusuf, Ari Azhar; Zahri, Ahmad Fauzan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study discusses Ignác Goldziher's criticism of qirā'āt (variations in Qur'anic recitation) and its implications for Islamic education. Orientalist criticism, including Goldziher's view, emphasises that the diversity of qirā'āt is due to the weakness of early Arabic orthography that lacks dots and harakat, so it is considered a product of human improvisation, not a divine provision. This criticism raises doubts about the authenticity of the Qur'an and has a significant impact on the younger generation of Muslims if not responded to with scientific arguments. This study aims to analyse 'Abd al-Fattāḥ al-Qāḍī's thoughts as a critical response to Goldziher's views, as well as explore its implications in strengthening the teaching of qirā'āt in Islamic educational institutions. This research uses a qualitative method with a library research approach. Primary data is taken from Goldziher's Madhāhib al-Tafsīr al-Islāmī and al-Qirā'āt fī Naẓr al-Mushtashriqīn wa al-Mulḥidīn by 'Abd al-Fattāḥ al-Qāḍī, as well as other supporting literature. The results show that Goldziher's critique is ahistorical and ignores the talaqqī system and mutawātir sanad in the Islamic tradition. In contrast, al-Qāḍī asserts that the variations in qirā'āt are varied, not contradictory, and have wisdom in facilitating the understanding of the Qur'an. This study recommends integrating traditional and critical academic approaches into the Islamic education curriculum. The traditional approach emphasises memorisation and talaqqī, while the critical approach equips students with scientific abilities to respond to orientalist criticism. This research makes a significant contribution in filling the gap of previous descriptive research and offering practical solutions for strengthening qirā'āt education in facing the challenges of orientalist thought.